Investigating the influence of meteorological parameters on the accuracy of sea-level prediction models in Sabah, Malaysia - Muslim T.O.; Ahmed A.N.; Malek M.A.; Afan H.A.; Ibrahim R.K.; El-Shafie A.; Sapitang M.; Sherif M.; Sefelnasr A.; El-Shafie A. (MDPI, 2023)
artificial intelligence; artificial neural network; cloud cover; meteorology; prediction; sea level change; East Malaysia; Kota Kinabalu; Kudat; Malaysia; Sabah